EFEKTIVITAS PENGOPERASIAN INSTALASI PENGOLAH AIR LIMBAH (IPAL) PERUSAHAAN PERAIH SERTIFIKASI ISO 14001 DI KAWASAN SIMONGAN KOTA SEMARANG (The Effectivity of Waste Water Treatment Plan Operated by Industrial Companies Holding ISO 14001 Certificate) - Zaenuri Zaenuri (Jurnal Manusia dan Lingkungan, 2012)
ABSTRAKPenelitian ini bertujuan untuk menganalisis efektivitas pengoperasian instalasi pengolah air limbah (IPAL) perusahaan peraih sel1ifikasi ISO 14001 di Kawasan Simongan Kota Semarang. Data yang diperoleh dianalisis secara deskriptif-komparatif dan inferensial dengan menggunakan uji-t. Hasil penelitian menunjukkan, pada perusahaan farmasi, rata-rata konsentrasi TSS, BOD, dan COD periode 1989-1998 (sebelum memperoleh ISO 14001) masing-masing sebesar 92,3229 mg/I, 45,5022 mg/I, dan 87,3691 mg/I, sedangkan rata-rata pH sebesar 7,2388. Parameter BOD dan COD memenuhi baku mutu, pH dalam interval baku mutu yang ditetapkan, sedangkan TSS berada di atas baku mutu.ABSTRACTThis research was intended to analyze the effectivity of  waste water treatment plan operated by industrial companies holding ISO 14001 certificates in Simongan Area of SemarangCity. The data were analyzed descriptively, comparatively and inferentially using t-tests. The analyses showed that prior to obtaining ISO 14001 certificate (1989-1998), the pharmaeutical company had its average concentrations of TSS, BOD, and COD of 92.3229, 45.5022 and 87.3691 mg/l respectively, with an average pH of 7.2388. These parameters of BOD and COD had already met the prevailing standard qualities, the TSS parameter was above the standard quality, and the pH was within the prevailing standard quality interval. After obtaining the ISO 14001 certificate (2005-2008), this pharmaeutical company was able to maintain all of the key parameters to meet the prevailing stadard qualities. In case of the galvanizing company prior to obtaining ISO 14001 certificate (1989-1998), its average concentrations of TSS and CN were 256.3469 and 0.25575 mg/l respectively (above the prevailing standard qualities), those for total Cr, C+6, Cu, Zn, Ni, and Pb were 0.0510, 0.0036, 0.236060, 0.7242, 0.01790 and 0.0286 mg/l respectively (still under the prevailing standard qualities), while the an average pH was within the standard quality interval. After obtaining ISO 14001 certificate (2006-2008), this galvanizing company was able to improve all of the key parameters to meet the prevailing stadard qualities. It was then inferred that the water treatments were operated effectively by the two ISO 14001 certificate achievers.